Brief Education on Microvasculature and Pit Pattern for Trainees Significantly Improves Estimation of the Invasion Depth of Colorectal Tumors - Joon Sung Kim; Bo-In Lee; Hwang Choi; Bong Koo Kang; Jong In Kim; Hae Mi Lee; Eun-Joo Im; Byung-Wook Kim; Sang-Woo Kim; Myung-Gyu Choi; Kyu Yong Choi (Gastroenterology Research and Practice)
Objectives. This study was performed to evaluate the effectiveness of education for trainees on the gross findings identified by conventional white-light endoscopy (CWE), the microvascular patterns identified by magnifying narrow-band imaging endoscopy (MNE), and the pit patterns identified by magnifying chromoendoscopy (MCE) in estimation of the invasion depth of colorectal tumors. Methods. A total of 420 endoscopic images of 35 colorectal tumors were used. Five trainees estimated the invasion depth of the tumors by reviewing the CWE images before education. Afterwards, the trainees estimated the invasion depth of the same tumors after brief education on CWE, MNE and MCE images, respectively. Results. The initial diagnostic accuracy for deep submucosal invasion before education and after education on CWE, MNE, and MCE findings was 54.3%, 55.4%, 67.4%, and 76.6%, respectively. The diagnostic accuracy increased significantly after MNE education (P=0.028). The specificity for deep submucosal invasion before education and after education on CWE, MNE, and MCE findings was 47.9%, 45.7%, 65.0%, and 80.7%, respectively. The specificity increased significantly after MNE (P=0.002) and MCE (P=0.005) education. Conclusion. Brief education on microvascular pattern identification by MNE and pit pattern identification by MCE significantly improves trainees’ estimations of the invasion depth of colorectal tumors.